Evaluating the reusability of carbon black recovered from waste tyres: An elemental and microstructural analysis - Olusola Olayemi Fadipe; Kehinde Adenike Oyewole; Abiola Usman Adebanjo; Ayotunde Taiwo Ajiferuke; Olakunle Olukayode (Results in Surfaces and Interfaces)
Pyrolysis-recovered carbon black (RCB) was retrieved from waste tyres (WTs) collected from landfills, where they are deposited in large quantities. WTs were mechanically reduced into powdery samples and subjected to proximate and ultimate analyses before pyrolysis. Subsequently, the WTs samples were pyrolyzed for 2 h at 400 °C (RCB 400), 500 °C (RCB 500), and 600 °C (RCB 600), respectively in a locally fabricated pyrolysis chamber. Scanning Electron Microscopy (SEM), energy-dispersive spectroscopy (EDS), X-ray diffraction (XRD), and Raman spectroscopy analysis (RSA) were employed to examine the microstructure and elemental composition of the pelletized RCB. Thereafter, the economic value of RCBs was explored based on previous literature. The results of the proximate and ultimate analyses showed that WTs have a moisture content of 0.22%, an ash content of 0.099%, a volatile matter content of 3.975%, a fixed carbon content of 95.71%, and a mean carbon content of 83.695%, indicating that a high percentage of carbon black can be recovered. SEM and EDS tests revealed that RCB 400 had a less porous morphology and exhibited a maximum carbon content of 84.87% (w%). Furthermore, XRD and RSA demonstrated a structural transition from an amorphous state to a graphitized crystalline form as the pyrolysis temperature increased from 400 °C to 600 °C. The presence of crystalline structures with strong C–C aliphatic bonds, strong S–S bonds, and mild anhydride bonds was observed. From an economic standpoint, the low concentration of impurities in the RCBs derived from WTs constitutes a challenge. However, this does not negate the potential for significant gains, such as cost reduction and a lower carbon footprint, when RCBs are used as partial substitutes for commercial carbon blacks in manufacturing processes.